Impact on Quality of Life of Oral Diseases Related to Stress - Rivera-Reza DDS, Diana I. (2020)
It has been suggested that oral mucosa diseases related to stress have a negative impact on the quality of life. However, the information regarding which aspects are the most affected is inconclusive. The objective was to compare the quality of life associated with oral health in two groups: Cases formed by 21 patients coming from a teaching clinic, suffering oral lichen planus, recurrent aphthous stomatitis, and burning mouth syndrome; Control formed by 42 healthy subjects matched for age and gender. Oral Health Impact Profile questionnaire was applied. Statistical analysis showed that group Cases has worse quality of life (p 0.03) than the one of controls, specifically on psychological discomfort (p 0.027), physical disability (p 0.004); and handicap dimensions (p 0.002; RM 5.63 IC1.58-20.80). It was concluded that patients suffering oral mucosa disease related to stress showed poor quality of life.